Gold nanotriangles: scale up and X-ray radiosensitization effects in mice. Issue 16 (30th January 2017) - Bhattarai, S. R.; Derry, P. J.; Aziz, K.; Singh, P. K.; Khoo, A. M.; Chadha, A. S.; Liopo, A.; Zubarev, E. R.; Krishnan, S.
Abstract : Intravenously administered gold nanotriangles accumulate passively in tumors in mice and potently sensitize them to radiation therapy. Abstract : Abstract In the past decade, there has been considerable interest in radiosensitization using gold nanoparticles that accumulate specifically in cancerous tissue while sparing normal tissues. Despite this interest, it remains unclear which nanoparticle morphologies, cellular uptake, or cytoplasmic distribution elicit optimal radiosensitization. We introduce gold nanotriangles (AuNTs) as a possible X-ray radiotherapy sensitizer. In this study, we first explored a large-scale synthetic method for the production of high quality monodisperse AuNTs. Second, we conducted in vitro and in vivo experiments to evaluate the effect of PEGylated AuNTs (pAuNTs) on cellular uptake, cytotoxicity, bio-distribution, and radiosensitization on radiation-resistant human Glioblastoma Multiforme (GBM) cells. Our results suggest that the new scale up synthesis methodology consistently produced high quality AuNTs and pAuNTs which had nonspecific cellular uptake without any obvious cytotoxicity and exhibited excellent radiosensitization.